Beyond the invisible hand : groundwork for a new economics - Basu, Kaushik (Princeton, NJ : Princeton University Press, 2010)
One of the central tenets of mainstream economics is Adam Smith's proposition that, given certain conditions, self-interested behavior by individuals leads them to the social good, almost as if orchestrated by an invisible hand. This deep insight has, over the past two centuries, been taken out of context, contorted, and used as the cornerstone of free-market orthodoxy. In Beyond the Invisible Hand, Kaushik Basu argues that mainstream economics and its conservative popularizers have misrepresented Smith's insight and hampered our understanding of how economies function, why some economies fail.
Cover -- Contents -- Preface -- Chapter 1 In Praise of Dissent -- Discontent and Discourse -- Smith's Myth -- The Lay of the Land -- On Understanding -- Chapter 2 The Theory of the Invisible Hand -- Competition and Social Welfare -- The Standard Critiques -- Chapter 3 The Limits of Orthodoxy -- The Dual Interpretation -- Evolving Feasible Set -- Evolving Preference -- Social Norms and Culture -- A Comment on Incentive Compatibility -- On Methodological Individualism -- On Knowledge -- Chapter 4 The Economy according to Law -- Kafka's Invisible Hand -- Law's Economy: The Standard View -- The Law as Focal Point -- Implications of the Focal View of Law -- A Game-Theoretic Illustration of Law as Focal Point -- A Research Agenda -- Chapter 5 Markets and Discrimination -- Do Free Markets Reduce Discrimination? -- The Literature -- The Self-Reinforcement of Productivity -- The Entrepreneur -- Toward a New Theoretical Model -- Appendix: Aptitude Test Administered to Slum Children at Anandan in Calcutta -- Chapter 6 The Chemistry of Groups -- Identity and Methodological Individualism -- The Ingredients of Theory -- Altruism, Trust, and Development -- The Janus Face of In-group Altruism -- The Malignancy of Identity -- Chapter 7 Contract, Coercion, and Intervention -- Principle of Free Contract -- Coercion and Voluntariness -- The Large Numbers Argument -- Acts and Rules -- Multiple Equilibria -- Domains of Intervention -- Chapter 8 Poverty, Inequality, and Globalization -- Governance and the Globe -- Inequality -- Some Facts of Globalization -- Some Analytics of Globalization -- Inequality and Poverty: The Quintile Axiom -- Poverty-Minimizing Inequality, with or without Globalization -- Policy Implications -- Chapter 9 Globalization and the Retreat of Democracy -- Democracy in Deficit -- Globalization and Influence -- Dollarization and Democracy -- Democratic Global Institutions -- Chapter 10 What Is to Be Done? -- Interpreting the World and Changing It -- The 'Environmental Case' against Inequality -- Despair and Hope -- Notes -- References -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Economics; Economic policy; Economics; Économie politique; Politique économique.; economics; BUSINESS & ECONOMICS -- Economics -- Theory; BUSINESS & ECONOMICS -- Economic History; Economic policy; Economics; Unsichtbare Hand; Wirtschaftliches Verhalten; Wirtschaftstheorie; Economische politiek; Wirtschaftswissenschaften; Wirtschaftspolitik; Wirtschaftstheorie; Verhaltensökonomik.; Wirtschaftliches Verhalten; Electronic books